Efektivitas Pemanfaatan Dana Desa dalam Penyediaan Barang Publik Berbasis Kearifan Lokal: Studi Kasus Desa Nagaleah, Kabupaten Barito Timur - Fendy Hariatama; Rinto Alexandro; Tonich Tonich (FKIP, Universitas Palangka Raya, 2026)
This study aims to analyze the effectiveness of Village Fund utilization in providing public goods based on local wisdom and its implications for strengthening community economic literacy in Nagaleah Village, East Barito Regency. The research employed a qualitative approach using a case study method, with data collected through in-depth interviews, observation, and documentation. Data analysis was conducted descriptively and analytically by linking empirical findings to public economics theory, fiscal decentralization, and community economic education. The findings indicate that the utilization of Village Funds in Nagaleah Village is relatively effective in providing essential public goods that align with community needs. This effectiveness is influenced not only by planning and budget management but also by the integration of local wisdom, such as mutual cooperation and deliberation, which function as social capital. These values encourage community participation, strengthen a sense of ownership over public goods, and serve as a medium for informal economic learning in understanding budget management and development priorities. This study concludes that Village Funds play a strategic role not only as a fiscal policy instrument at the village level but also as a means of strengthening community-based economic education. The findings contribute to policy discussions on improving the quality of public spending, community participation, and economic literacy in rural development